Literature Review of Factors Affecting Capital Expenditure in Indonesia - Siti Aminah; Abdul Manan; Endang Astuti (Indonesian Development Economics and Localities, 2025)
This study reviews various research on the impact of financial variables on capital expenditure across different regions in Indonesia. The variables investigated include General Allocation Funds (DAU), Regional Original Income (PAD), Special Allocation Funds (DAK), and Profit Sharing Funds (DBH). The research primarily uses secondary data from financial reports, including the Realization Report of the Regional Budget (APBD) and financial statements from regional governments. Methods used across the studies include multiple regression analysis, moderated regression analysis, and panel data models with various statistical tests such as the Chow test, Hausman test, and Lagrange Multiplier test. The findings indicate that DAU and PAD generally have a positive impact on capital expenditure, while the effects of DAK and DBH vary, with some studies showing positive impacts and others indicating negligible or negative effects. The moderating factor of Remaining Over Budget Financing (SILPA) presents mixed results. The reviewed studies highlight a gap in comparative analysis across different regions and suggest a need for further exploration of the interaction between economic conditions and financial variables, as well as the impact of long-term economic cycles on capital expenditure. Addressing these gaps could enhance understanding and inform more effective fiscal management and resource allocation strategies.